IoT Creating an Ingenious, Collaborative and Congruent World - Mangal, Anu; Bhagat, Tanushri; Valuskar, Srishti; Rizvi, Dr. M.A (International Journal of Computer Sciences and Engineering, 2019)
When wireless is perfectly applied, the whole earth will be converted into a huge brain, which in fact it is, things being particles of a real and rhythmic whole and the instruments through which we shall be able to do this will be amazingly simple and compact so that it could be carried in the vest pocket.” – Nikola Tesla. The Internet of Things is the smart interconnection of things over the present and future Internet infrastructure. IoT has the ability to revolutionize complete human life in every domain of present life and even beyond imagination. It allows smart human lives allowing communication between objects, machines and everything together with people. With the evolution of the Internet to cover the real-world, many new services will be enabled that will completely ameliorate people’s everyday lives, generate new businesses opportunities, and make cities, buildings and transport smarter. This fantastic opportunity provides some security challenges also. This paper analyzes the basic working and features of Internet of Things. Trends in the Internet of Things with the goal of scrutinizing and inspecting their privacy implications are also discussed. Later, the impact that Internet of Things in our day to day lives is discussed, pointing out the challenges that need to be overcome to ensure that the Internet of Things becomes a benison reality.